Traceability system in halal procurement: A bibliometric review - Ilyas Masudin; Bima Bagos Rahmatullah; Muhammad Armand Agung; Inka Amalia Dewanti; Dian Palupi Restuputri (Logistics, 2022)
Background: The increasing Muslim population worldwide will increase the Islamic market share in the future. Thus, the higher demand for halal food has caused the food industry to pay attention to the quality control system for the ingredients used. This paper aims to review the previous literature regarding the traceability system for halal suppliers in the food supply chain to achieve the specified halal standards. It discusses the literature review as a method for conducting research and offers an overview of different types of reviews, as well as some guidelines to both conduct and evaluate a literature review. Methods: The method uses a sample of about 200 articles from the structured literature study period in 2007-2021. We use Perish application to identify journals, articles, citations, authors, and keywords. Results: The analysis reveals five research topic clusters: traceability, halal supply chain, food supply chain, halal logistics, and halal lifestyle. There is a strong relationship between procurement and traceability. Procurement is related to the food industry and halal traceability. The food product traceability system provides transparency in food manufacturing, enabling customers to trust halal product claims. The results show that food supply chain information systems can enable traceability and transparency. Conclusions: The review of this analysis is related to the supplier traceability system in the halal-food-production supply chain, which can help explore halal supplier issues and trends. For future research, technology can be used within a traceability system in the halal food industry, such as data interchange, radio frequency identification, and blockchain.
Keywords: 650; halal; halal logistics; halal suppliers; procurement; traceability